A rapid and highly sensitive method for simultaneous determination of bioactive constituents in leaf extracts of six Ocimum species using ultra high performance liquid chromatography-hybrid linear ion trap triple quadrupole mass spectrometry. Issue 2 (1st December 2015) - Pandey, Renu; Chandra, Preeti; Kumar, Brijesh; Dutt, Bhupender; Sharma, Kulwant Rai
Abstract : Ocimum species have tremendous value in pharmaceutical, perfumery, food processing and cosmetic industries, also in traditional rituals and medicines. Abstract : Ocimum species have tremendous value in pharmaceutical, perfumery, food processing and cosmetic industries, also in traditional rituals and medicines. These are a rich source of terpenoids and phenolic compounds. Therefore, determination of these bioactive constituents is significant for quality evaluation of Ocimum species. In this study, we have developed and validated a rapid and highly sensitive method for simultaneous determination of sixteen bioactive constituents in the leaf extracts of six Ocimum species using ultra high performance liquid chromatography-hybrid linear ion trap triple quadrupole mass spectrometry (UHPLC-QqQLIT -MS/MS). The developed method is applied in the leaf extracts of six Ocimum species to investigate variations in the content of sixteen bioactive constituents. Quantitative analysis was performed by UHPLC-QqQLIT -MS/MS operating under multiple reaction monitoring mode in negative electrospray ionization. Chromatographic separation was accomplished on an Acquity UPLC BEH C18 column using a gradient elution of 0.1% formic acid in water and 0.1% formic acid in acetonitrile. The calibration curves of all sixteen analytes showed good linearity ( r 2 ≥ 0.9989) over the concentration range of 0.5–500 ng mL −1 . The intra- and inter-day precisions and accuracy were within RSDs ≤ 1.95% and ≤ 1.68%, respectively. The results indicated that ursolic acid and rosmarinic acid were the major constituents in almost all the investigated Ocimum species except for O. americanum . All the results obtained from this study demonstrated that the developed method is rapid, sensitive and efficient for the quantification of multiple constituents. Therefore, it could be reliably utilized for the quality control and authenticity establishment of Ocimum species.